Exploring the role of adaptation technologies and energy poverty on environmental quality: progress toward sustainable development goals - Ahsan Anwar; Afshan Hamid; Arshian Sharif; Sook Fern Yeo; Kay Hooi Keoy; Tat-Huei Cham; Qasim Raza Syed (Humanities & Social Sciences Communications)
Abstract The intensifying issue of global warming is worsened by the fast economic growth of the world’s leading economies, which have emerged as the most polluted countries globally. The present study has tried to make an intensive environmental analysis of the selected five most polluted countries of the world—China, Russia, the United States, India, and Japan to see how adaptation technology (ATEC) and alleviating energy poverty (EPO) help these countries to raise their environmental quality. The study hypothesizes that ATEC raises the environmental quality of these countries while controlling energy poverty is also required. The study also delves into the impact of the financial development (FD) of these selected countries on the environmental quality of these polluted economies. The study covers the period from 2000 to 2020. To generate a comprehensive set of outcomes, the study has utilized the panel quantile regression (PQR) approach, which is better suited to handle data non-normality and the existence of outliers, which is most expected in using a dynamic set of variables. The outcomes of the study confirm the constructive role of ATEC and the need for controlling energy poverty in the most polluted countries to raise their environmental quality. Following the empirical outcomes, the study proposes the policy framework for not only enhancing environmental quality but also securing several SDGs like SDG 01 working for no poverty, SDG 07 aimed at making green energy affordable, SDG 09 concerns industrial development with innovation and infrastructure, SDG 12 assured responsible consumption as well as production, SDG 13 considered climate actions, and SDG 17 forced partnership for goals, particularly in the five most polluted countries.